PENDIDIKAN ANAK USIA DINI MENURUT PSIKOLOGI ISLAMI - Bahril Hidayat; Ary Antony Putra; Musaddad Harahap (UIR PRESS, 2018)
The relationship among early childhood education is related to the Islamic Education and Islamic Psychology perspective. Discussion of this article forms of theoretical review and expected to generate scientific reference to formulate explanation and development of science about Islamic Early Childhood Education according to Islamic Psychology. Islamic Education into early childhood as students, not only based on the principles of western Educational Psychology and Psychology of Learning (Psychology Learning and Teaching) from the Western scientist theory, but must be based on Islamic values and concept too. By applying the concept, the internalization of Islamic Education into the psychophysiological of early childhood will be achieved. According to the integration of principles of science and Islam through 5 Strategic Development of Islamic Education for Early Childhood Based on Islamic Psychology Principles, namely, 1) awakening learners' self-awareness about Islam, 2) involves the educational environment in to the learning activities, 3) understanding the child's age development by the method of playing, 4) using techniques that appeal to early childhood, 5) directing the child to develop their unique potential.